A new species of the genus Clubiona Latreille (Araneae, Clubionidae) from Hainan Island, China - Zhu, Biran; Ren, Haiqing; Chen, Jian (Zootaxa, 2012)
The genus Clubiona Latreille, 1804 is the biggest genus of Clubionidae and the only genus reported from China till now. According to Platnick (2011), a total of 578 species have been described from all over the world, of which 100 species were reported from China (Song et al. 1999). Various field collections in Hainan Island, China were carried out by the colleagues of Hubei University in 2010. During these we have found a Clubiona species, which has a wing-shaped femoral apophysis and is described here as new to the science.